2010
DOI: 10.1016/j.electacta.2010.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of acridine-calix[4]arene with DNA at the electrified liquid|liquid interface

Abstract: The behaviour of an acridine-functionalized calix [4]arene at the interface between two immiscible electrolyte solutions (ITIES) is reported. Molecular modelling showed that the acridine-calix[4]arene has regions of significant net positive charge spread throughout the protonated acridine moieties, consistent with it being able to function as an anion ionophore.The presence of this compound in the organic phase facilitated the transfer of aqueous phase electrolyte ions. Upon addition of double stranded DNA to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Calixarene-facilitated IT was diminished by the complexation with DNA, providing the basis for DNA hybridization detection at ITIES. (152) Interactions of chitosan with picrate and eosin were recently characterized at ITIES, (153) and extraction of heparin molecules (molecular weights up to 20 kDa) facilitated by a carefully designed ionophore has been demonstrated, aiming into a development of amperometric heparin sensor. (154) These recent developments demonstrate that electrochemistry at ITIES has many potential applications for electroanalytical macromolecule sensing, and they offer a new approach for characterization of macromolecules.…”
Section: Macromolecule Sensingmentioning
confidence: 99%
“…Calixarene-facilitated IT was diminished by the complexation with DNA, providing the basis for DNA hybridization detection at ITIES. (152) Interactions of chitosan with picrate and eosin were recently characterized at ITIES, (153) and extraction of heparin molecules (molecular weights up to 20 kDa) facilitated by a carefully designed ionophore has been demonstrated, aiming into a development of amperometric heparin sensor. (154) These recent developments demonstrate that electrochemistry at ITIES has many potential applications for electroanalytical macromolecule sensing, and they offer a new approach for characterization of macromolecules.…”
Section: Macromolecule Sensingmentioning
confidence: 99%
“…In recent years there have been many reports on the behaviour and detection of biomolecules at the ITIES. The detection of a range of biomolecules including amino acids [19], heparin [20,21], protamine [22,23], haemoglobin [24,25], lysozyme [26,27], insulin [28], dopamine [29][30][31], noradrenaline [31] and DNA [32] have been reported at the ITIES.…”
Section: Introductionmentioning
confidence: 99%
“…O'Sullivan and Arrigan [107c] showed that w/PVC-DCH interfaces modified with AOT -showed an increase of the faradaic current (6-fold) and interfacial coverage (17-fold) for the detection of myoglobin which confirmed the ability of protein-surfactant complexes to enhance the electrochemical signal. On the other hand, cationic surfactants were reported to bind DNA [22,114] although little additional work has been carried out in this direction.…”
Section: Detection Of (Bio)macromoleculesmentioning
confidence: 99%
“…1) have been widely used for the characterisation of ions or ionisable compounds such as drugs, [19] amino acids, [20] proteins, [21] and DNA. [22] The use of electrochemical methods at the macro-ITIES has been shown to be powerful for exploration of electrocatalysis [23] and the basis of spectrochemical analysis, [24] as well as investigation of the behaviours of inorganic ions and biomolecules at liquid−liquid interfaces. [7,25] For example, Hartvig et al [21a] studied the interaction between lysozyme and two lipophilic ions at the oil−water interface using cyclic voltammetry and electrochemical impedance spectroscopy at such a macro-ITIES.…”
Section: Experimental Systemsmentioning
confidence: 99%